Chronic Respiratory Diseases in the Regions of Northern Russia: Epidemiological Distinctions in the Results of a National Population Study - Marine H. Gambaryan; Svetlana A. Shalnova; Alexander D. Deev; Oxana M. Drapkina (International Journal of Environmental Research and Public Health, 2017)
The aim of the study is to investigate the epidemiological situation regarding chronic respiratory diseases in populations that inhabit different climatic–geographical regions of Russia, and to develop targeted programs for prevention of these diseases. Methods: (1) a comparative analysis of the standardized mortality data in Russia and other selected regions of the Russian North using the European standard for respiratory diseases, in a population aged 25–64; and (2) data from a randomized cross-sectional epidemiological study, with subjects from three different climatic-geographical regions of Russia. Results: (1) the respiratory disease-related mortality rates in the majority of Russian Northern regions were much higher compared to the national average. Although death rates from chronic lower respiratory diseases were higher among the Northern regions and in the whole of Russia relative to the countries of European Union (EU), the cause of death in the populations of the Northern regions tend to be lower respiratory infections and pneumonia; and (2) despite the absence of any significant differences in the prevalence of smoking, the prevalence of chronic respiratory diseases (COPD) is significantly higher in Far North Yakutsk compared to the other two regions in this study—Chelyabinsk and Vologda. The status of hyperborean had the highest chance of a significant contribution to COPD and cardiorespiratory pathology among all other risk factors. The results revealed a need for effective targeted strategies for primary and secondary prevention of chronic respiratory diseases for the populations of the Northern regions of Russia. Conclusions: The revealed regional distinctions regarding the prevalence of, and mortality from, chronic respiratory diseases should be taken into consideration when designing integrated programs for chronic non-communicable disease prevention in these regions.